Compliance with the cardiology residency training program during the COVID-19 pandemic, Lima–Peru - Olortegui Yzu, Adriel (2022)
Objective. To characterize compliance with the annual curricular program of second and third-year cardiology residents in hospital of Lima—Peru during the COVID-19 pandemic. Materials and methods. A cross-sectional study was conducted, through a questionnaire applied to seventy-eight cardiology residents from the second and third year of specialty. We evaluated the compliance with rotations in clinical fields, individual compliance with the annual program, and the achievement of minimum training standards. Results. Compliance with rotations in clinical fields was highly variable (from 7.9% in Cardiac Rehabilitation for the second year to 90.9% for imaging in cardiology). Regarding individual compliance, 98.7% did not manage to comply with the annual program. Finally, only the standard of evaluation by radionuclides of myocardial function and perfusion was achieved by all residents, concerning the scope of the other achievements, variations are reported from 4.4% for performing stress tests to 75.8% in the to participate in interventional cardiology procedures. Associations were found between compliance with rotations with the type of health organization and type of university. Conclusions. The COVID-19 pandemic has considerably affected the training of cardiology residents, mainly due to non-compliance with the annual curriculum.